Measurement of the W W cross section in root s=7 TeV pp collisions with the ATLAS detector and limits on anomalous gauge couplings - Onofre, A. (2012)
This Letter reports a measurement of the WW production cross section in View the MathML sources=7 TeVpp collisions using data corresponding to an integrated luminosity of 1.02 fb−1 collected with the ATLAS detector. Using leptonic decays of oppositely charged W bosons, the total measured cross section is View the MathML sourceσ(pp→WW)=54.4±4.0(stat.)±3.9(syst.)±2.0(lumi.) pb, consistent with the Standard Model prediction of σ(pp→WW)=44.4±2.8 pbσ(pp→WW)=44.4±2.8 pb. Limits on anomalous electroweak triple-gauge couplings are extracted from a fit to the transverse-momentum distribution of the leading charged lepton in the event.